2021
DOI: 10.1155/2021/2637577
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Peptide F2d Isolated from Rice Residue Exerts Antioxidant Effects via Nrf2 Signaling Pathway

Abstract: Studies have shown that the peroxidation caused by oxygen free radicals is an important reason of vascular endothelial dysfunction and multiple diseases. In this study, active peptides (F2ds) were isolated from the fermentation product of rice dregs and its antioxidant effects were approved. Human umbilical vein endothelial cells (HUVECs) stimulated by H2O2 were used to evaluate the antioxidation effect and its molecular mechanism in the oxidative stress model. F2d protected H2O2-induced damage in HUVECs in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In response to oxidative stress, Nrf2 is decoupled from cytosolic repressor protein Keap1 and transfers to the nucleus, binding with the ARE and subsequently activating downstream related gene transcriptions, such as catalase (CAT), heme oxygenase-1 (HO-1), superoxide dismutase (SOD), glutathione (GSH), and other cytoprotective enzymes, thereby preventing the cells from oxidative stress damage [ 11 , 12 ]. Liu et al isolated a new type of bioactive peptide F2d from rice residue, which acted on umbilical vein endothelial cells and exerted antioxidant stress function through promoting Nrf2 signal pathway [ 13 ]. A recent study found that a small molecule SR9009 blocks cellular senescence via the Nrf2 pathway in vitro and in vivo [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In response to oxidative stress, Nrf2 is decoupled from cytosolic repressor protein Keap1 and transfers to the nucleus, binding with the ARE and subsequently activating downstream related gene transcriptions, such as catalase (CAT), heme oxygenase-1 (HO-1), superoxide dismutase (SOD), glutathione (GSH), and other cytoprotective enzymes, thereby preventing the cells from oxidative stress damage [ 11 , 12 ]. Liu et al isolated a new type of bioactive peptide F2d from rice residue, which acted on umbilical vein endothelial cells and exerted antioxidant stress function through promoting Nrf2 signal pathway [ 13 ]. A recent study found that a small molecule SR9009 blocks cellular senescence via the Nrf2 pathway in vitro and in vivo [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aromatic amino acids and hydrophobic amino acid residues in the peptides could significantly increase the antioxidant activity, thereby inducing hydrogen atoms (Fontoura et al, 2019;Yang et al, 2020). Peptides can activate the Nrf2 pathway by downregulating the Keap1 gene and upregulating the Nrf2 gene expression to achieve antioxidant effects (Figure 3B) (Liu et al, 2021). Mushrooms are the primary sources of natural active peptides with significant potency, high tissue affinity, low toxicity, and high stability (Zhou et al, 2020).…”
Section: Peptidesmentioning
confidence: 99%
“…The 2,2-diphenyl-1-picrylhydrazyl DPPH free radical and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) ABTS+ free radical scavenging tests were carried out using GLP4 and methylated-GLP4, and the active site of GLP4 was methylated as previously described. 29…”
Section: Methodsmentioning
confidence: 99%
“…The level of ROS was undertaken according to a previously described method. 29 DCFH-DA diluted 1 : 1000 in serum-free medium was added to each dish, incubated with cells for 20 min at 37 °C in a cell incubator, and washed with serum-free cell medium to remove extracellular DCFH-DA. The fluorescence intensity of HUVECs was detected by a fluorescence microscope (Nikon, Ti2-E, Japan) and a microplate reader (Molecular Devices, SpectraMax i3x, USA).…”
Section: Methodsmentioning
confidence: 99%